Many Europes : - Dutton, Paul Edward (McGraw-Hill Companies, 2014)
Many Europes, Choice & Chance in Western Civilization, an entirely integrated program, we recognize this changing environment and set out with the goal of better meeting the western civilization course challenges of improving student performance, critical analysis skills, and overall comprehension in a continually evolving teaching and learning environment.